Prognostic Importance of the Preoperative Naples Prognostic Score for Patients With Adenocarcinoma of the Esophagogastric Junction - Xiong, Jianping; Wang, Yaqin; Kang, Wenzhe; Ma, Fuhai; Liu, Hao; Ma, Shuai; Li, Yang; Jin, Peng; Hu, Haitao; Tian, Yantao (Frontiers in Oncology, 2020)
Background: The naples prognostic score (NPS) is established according to nutritional or inflammatory state, and it is identified as the new prognostic score for a variety of malignant tumors. However, its significance in cases suffering from adenocarcinoma of esophagogastric junction (AEJ) who receive surgery remains unclear so far. Methods: In this study, patients receiving surgery without preoperative therapy were examined between June 2007 and August 2017 in a retrospective way. Typically, the serum albumin level, total cholesterol level, neutrophil-to-lymphocyte ratio, together with the lymphocyte-to-monocyte ratio, was determined to calculate the NPS. The prognostic impact of NPS was evaluated using survival analyses. Time-dependent receiver operating characteristic curve (t-ROC) analysis was also carried out for comparing prognostic impacts of those scoring systems. Results: Altogether 231 cases were enrolled in this study. A higher NPS showed positive correlation with perineural invasion. Upon multivariate analysis, NPS was identified to be the independent prognostic factor to predict overall survival (OS) along with relapse-free survival (RFS) (both P< 0.05), and an especially strong correlation was observed at advanced pTNM tages based on NPS system. As for subgroup analyses on adjuvant chemotherapy or surgery only, NPS still independently predicted the OS as well as RFS (both P< 0.05) in both groups. Furthermore, t-ROC analysis showed that NPS was more accurate than the systemic inflammation score in predicting OS and RFS. Conclusions: The NPS represents the simple and useful rating system, which can independently predicts the survival for AEJ cases undergoing surgery.